(untitled) (Revista Apotheke, 2021)
This article weaves relationships between teaching experience and theoretical studies in order to fundamentally analyze the experiences of the Supervised Curricular Internship I, a discipline in the Visual Arts degree course at the State University of Santa Catarina (UDESC). The pedagogical performance resulting from the discipline took place in Early Childhood Education, at the Municipal Child Education Center (NEIM) Hassis, located in Florianópolis-SC. The pedagogical theories that influenced the research in the internship are related to works by John Dewey (1932, 1959, 1979a, 1979b) and supported by contemporary authors (CUNHA, CARVALHO), whom promote a progressive analysis of some of Dewey’s theories in philosophy and education.